(untitled) (The Peerian Journal, 2022)
the scientific article analyzes the main trends in the formation and development of non-governmental non-profit organizations in Uzbekistan. The role of independent media in the democratization of society and the improvement of the system of public relations is revealed. Also, the legal framework in this area and their implementation are the object of scientific research in this article.